Antibiotic treatment for 6 weeks versus 12 weeks in patients with pyogenic vertebral osteomyelitis: an open-label, non-inferiority, randomised, controlled trial. Issue 9971 (7th March 2015) - Bernard, Louis; Dinh, Aurélien; Ghout, Idir; Simo, David; Zeller, Valerie; Issartel, Bertrand; Le Moing, Vincent; Belmatoug, Nadia; Lesprit, Philippe; Bru, Jean-Pierre; Therby, Audrey; Bouhour, Damien; et al.
Summary: Background: Duration of treatment for patients with vertebral osteomyelitis is mainly based on expert recommendation rather than evidence. We aimed to establish whether 6 weeks of antibiotic treatment is non-inferior to 12 weeks in patients with pyogenic vertebral osteomyelitis. Methods: In this open-label, non-inferiority, randomised controlled trial, we enrolled patients aged 18 years or older with microbiologically confirmed pyogenic vertebral osteomyelitis and typical radiological features from 71 medical care centres across France. Patients were randomly assigned to either 6 weeks or 12 weeks of antibiotic treatment (physician's choice in accordance with French guidelines) by a computer-generated randomisation list of permuted blocks, stratified by centre. The primary endpoint was the proportion of patients who were classified as cured at 1 year by a masked independent validation committee, analysed by intention to treat. Non-inferiority would be declared if the proportion of cured patients assigned to 6 weeks of treatment was not less than the proportion of cured patients assigned to 12 weeks of treatment, within statistical variability, by an absolute margin of 10%. This trial is registered with EudraCT, number 2006-000951-18, and Clinical Trials.gov, number NCT00764114 . Findings: Between Nov 15, 2006, and March 15, 2011, 359 patients were randomly assigned, of whom six in the 6-week group and two in the 12-week group were excluded after randomisation. 176 patients assigned to the 6-week treatment regimen and 175 to the 12-week treatment regimen were analysed by intention to treat. 160 (90·9%) of 176 patients in the 6-week group and 159 (90·9%) of 175 of those in the 12-week group met the criteria for clinical cure. The difference between the groups (0·05%, 95% CI −6·2 to 6·3) showed the non-inferiority of the 6-week regimen when compared with the 12-week regimen. 50 patients in the 6-week group and 51 in the 12-week group had adverse events, the most common being death (14 [8%] in the 6-week group vs 12 [7%] in the 12-week group), antibiotic intolerance (12 [7%] vs 9 [5%]), cardiorespiratory failure (7 [4%] vs 12 [7%]), and neurological complications (7 [4%] vs 3 [2%]). Interpretation: 6 weeks of antibiotic treatment is not inferior to 12 weeks of antibiotic treatment with respect to the proportion of patients with pyogenic vertebral osteomyelitis cured at 1 year, which suggests that the standard antibiotic treatment duration for patients with this disease could be reduced to 6 weeks. Funding: French Ministry of Health.